2016
DOI: 10.1111/fwb.12847
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients associated with terrestrial dissolved organic matter drive changes in zooplankton:phytoplankton biomass ratios in an alpine lake

Abstract: Summary Dissolved organic matter (DOM) is increasing in many lakes due to climate change and other environmental forcing. A 21‐day microcosm experiment that manipulated terrestrial DOM was used to determine the effect of DOM on zooplankton:phytoplankton biomass ratios (z:p). We predicted that if DOM additions increase the amount of fixed carbon available for higher trophic levels through stimulation of the microbial loop and hence zooplankton, the z:p will increase. However, if DOM additions increase other n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 65 publications
2
34
1
1
Order By: Relevance
“…Yet results from similar leaching experiments support the trends that we found in wetland versus forest soils. Kissman et al () recorded C:N:P ratios of leachates from bog soils in montane forests ~167:11:1, supporting our conclusion that P enrichment relative to N may be more likely in wetland‐dominated landscapes. Qualls et al () found C:N:P ratios of soil leachates from the organic horizon in montane forests ~3601:76:1, supporting our conclusion that forest soils are relatively P poor.…”
Section: Discussionsupporting
confidence: 89%
“…Yet results from similar leaching experiments support the trends that we found in wetland versus forest soils. Kissman et al () recorded C:N:P ratios of leachates from bog soils in montane forests ~167:11:1, supporting our conclusion that P enrichment relative to N may be more likely in wetland‐dominated landscapes. Qualls et al () found C:N:P ratios of soil leachates from the organic horizon in montane forests ~3601:76:1, supporting our conclusion that forest soils are relatively P poor.…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, fish populations in lakes with higher allochthonous DOM inputs, especially those that are hydrologically connected to catchments with large C stocks, are to a larger degree supported by both (in variable proportion) bacterial and pelagic algal production (Karlsson et al., ; Solomon et al., ). Browning of lakes is leading to changes in basal production that propagate through food webs in lakes, including a shift from food webs dominated by autotrophs to food webs dominated by heterotrophic bacteria, and a shift from benthic to largely pelagic‐driven productivity (Ask et al., ; Karlsson et al., ; Kissman, Williamson, Rose, & Saros, ).…”
Section: Lower Food Quantitymentioning
confidence: 99%
“…Terrestrial and aquatic ecosystem dynamics are influenced by climatic change (e.g., Ball et al, 2010;Fritz & Anderson, 2013;Massaferro et al, 2013), land-use/vegetation alteration (e.g., Cooper et al, 2015;Kissman et al, 2017), and fire regime shifts (e.g., Araneda et al, 2013;Bixby et al, 2015;Brown et al, 2014) at multiple scales of space and time. Given the importance and the interconnectedness of both climate and fire (e.g., Emelko et al, 2016;Fletcher et al, 2014;Power et al, 2016), and terrestrial and aquatic ecosystems (Beck, Fletcher, Kattel, et al, 2018;Kissman et al, 2017;Strock et al, 2017), the paucity of research on how climate and fire drive terrestrial and aquatic ecosystem dynamics constitutes a critical knowledge gap that potentially undermines effective management and conservation endeavors. This lack of cross-cutting research is particularly salient in Australia, where fires are key ecological agent that both has shaped the unique flora of the region (Bowman, 2000) and threatens relict fire-sensitive plant systems with extinction (Holz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%